Hydrothermal Synthesis of Co3O4/ZnCo2O4 Core-Shell Nanostructures for High-Performance Supercapacitors. Issue 12 (2nd December 2021) - Lin, En-Syuan; Chao, Feng-Sheng; Liang, Chen-Jui; Chang, Chi-Jung; Fang, Alex; Lin, Chung-Kwei; Chang, Yu-Cheng; Tsay, Chien-Yie; Wu, Jerry J.; Chen, Chin-Yi
Abstract : Supercapacitive properties of Co/ZnCo oxide composite with a core–shell nanostructure (Co3 O4 /ZnCo2 O4 ) prepared directly onto a nickel foam substrate by a two-step hydrothermal method were investigated. The synthesized core–shell structure consisted of some ∼40–100 nm in thick flaky ZnCo2 O4 deposits coated onto the surface of Co3 O4 nanorods measuring ∼150 nm in diameter. The specific capacitance value of the Co3 O4 /ZnCo2 O4 core–shell nanostructure synthesized by hydrothermal at 130 °C for a ZnCo2 O4 deposition time of 2 h can attain 1804 F g −1 at a scan rate of 5 mV s −1 . Furthermore, the core–shell structured electrode still exhibited a relatively good capacitance retention of more than 93% after 3000 CV cycles due to the superior structural support of Co3 O4 scaffolds. The Co3 O4 /ZnCo2 O4 core–shell structure exhibits excellent electrochemical performances and, as such, is one of the more promising active materials in pseudocapacitor applications.